GODDESS OF THE JEWELLED WEB: THE TRANSMISSION OF THE TRANSPERSONAL IN VISIONARY ART - Mirante, Daniel (O Mosaico, 2023)
Via an inter-discourse between established concepts and liminal mythologies, tentative explorations are made on how visionary art transmits and perpetuates symbols of transpersonal experiences into culture. By using the concept of memes, cultural units that are transmitted through imitation and replication, we explore how visionary art facilitates and communicates liminal experiences with transformative impact upon established realities.